Akibat Hukum Implementasi Undang-Undang Nomor 11 Tahun 2020 terhadap Alih Fungsi Lahan Pertanian untuk Pembangunan Infrastruktur - Diyah Ayu Riyanti; Mutiara Ramadhani; Lailatul Fitriyah (CV Rewang Rencang, 2022)
The implementation of infrastructure development for the public interest requires large areas of land, but the land is generally already attached to land rights. So that there is a change of a land function. This raises questions about the implementation of Law No. 11 of 2020 on agricultural land conversion experts to support infrastructure development and the impact of agricultural land function. It is hereby concluded that the transfer of land functions is carried out in accordance with the provisions in the regulations. However, the function of agricultural land threatens food security in Indonesia due to the decreasing amount of agricultural land. Control of the function of agricultural land to create food security and sovereignty in order to increase the prosperity and welfare of farmers and the general public.